Proline C−H Bonds as Loci for Proline Assembly via C−H/O Interactions. (24th November 2022) - Daniecki, Noah J.; Bhatt, Megh R.; Yap, Glenn P. A.; Zondlo, Neal J.
Abstract: Proline residues within proteins lack a traditional hydrogen bond donor. However, the hydrogens of the proline ring are all sterically accessible, with polarized C−H bonds at Hα and Hδ that exhibit greater partial positive character and can be utilized as alternative sites for molecular recognition. C−H/O interactions, between proline C−H bonds and oxygen lone pairs, have been previously identified as modes of recognition within protein structures and for higher‐order assembly of protein structures. In order to better understand intermolecular recognition of proline residues, a series of proline derivatives was synthesized, including 4 R ‐hydroxyproline nitrobenzoate methyl ester, acylated on the proline nitrogen with bromoacetyl and glycolyl groups, and Boc‐4 S ‐(4‐iodophenyl)hydroxyproline methyl amide. All three derivatives exhibited multiple close intermolecular C−H/O interactions in the crystallographic state, with H⋅⋅⋅O distances as close as 2.3 Å. These observed distances are well below the 2.72 Å sum of the van der Waals radii of H and O, and suggest that these interactions are particularly favorable. In order to generalize these results, we further analyzed the role of C−H/O interactions in all previously crystallized derivatives of these amino acids, and found that all 26 structures exhibited close intermolecular C−H/O interactions. Finally, we analyzed all proline residues in the Cambridge Structural Database of small‐molecule crystal structures. We found that the majority of these structures exhibited intermolecular C−H/O interactions at proline C−H bonds, suggesting that C−H/O interactions are an inherent and important mode for recognition of and higher‐order assembly at proline residues. Due to steric accessibility and multiple polarized C−H bonds, proline residues are uniquely positioned as sites for binding and recognition via C−H/O interactions. Abstract : C−H bonds of proline are particularly favorable sites for C−H/O interactions, including intermolecular assembly and intramolecular structure stabilization. These C−H/O interactions, which occur at all proline ring positions, exhibit short H⋅⋅⋅O distances, and are significantly stabilized by stereoelectronic effects, with only a minor electrostatic contribution in solution.